Design and development of EDGAR - a telepresence humanoid for robot-mediated communication and social applications - Pang, Wee Ching (2020)
EDGAR is an acronym for «Expression Display & Gesturing Avatar Robot». It is an anthropomorphic telepresence humanoid, which is designed and implemented to allow for social expression. EDGAR is a robotic avatar that was developed by Nanyang Technological University for telepresence applications. It has a total of 28 degrees of freedom and it is able to mimic the remote user's head, torso, arms as well as fingers movements. EDGAR's head is a rear-projection system such that a face texture can be displayed on EDGAR's face. The remote user can use a normal webcam for live-streaming interaction as the face image can be processed to fit the contour of the face. This means that a person's facial features and expressions can be displayed on the robot, making EDGAR suited for portraying any person. EDGAR can also serve as a social robot. A virtual character's face can also be projected on the robot so that EDGAR can be used to perform autonomous social interactions with the people around it.